Design and analysis of a earthaquake simulator using hydraulic system [electronic resource] - 457611 Lim, Wai Seong (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2006